National consumption of opioid and nonopioid analgesics in Croatia: 2007–2013 - Krnic D; Anic-Matic A; Dosenovic S; Draganic P; Zezelic S; Puljak L (Dove Medical Press, 2015)
Darko Krnic,1 Andrea Anic-Matic,2 Svjetlana Dosenovic,2 Pero Draganic,1 Sasa Zezelic,1 Livia Puljak2 1Agency for Medicinal Products and Medical Devices, Zagreb, 2Laboratory for Pain Research, School of Medicine, University of Split, Split, Croatia Background: The increased consumption of analgesics has been documented worldwide during the last 2 decades. The aim of the study was to examine the trends in opioid and nonopioid analgesic consumption in Croatia between 2007 and 2013. Methods: Data on opioid consumption were extracted from the database of the national authority. All opioid and nonopioid analgesics were included in the analysis. Data were presented as defined daily doses per 1,000 inhabitants per day. Adequacy of opioid consumption was calculated using adequacy of consumption measure. Results: During the examined 7-year period, the total consumption and total cost of all analgesics in Croatia showed continuous increase. In the M01A group (anti-inflammatory and antirheumatic products, nonsteroids), ibuprofen had an exponential increasing trend, and in 2011, it overtook diclofenac consumption. Ibuprofen and diclofenac had the highest consumption also in the M02A group of topical products for joint and muscular pain. Tramadol was by far the most consumed type of opioids (N02A group) and paracetamol in the group of other analgesics and antipyretics (N02B). The adequacy of consumption measure value was 0.19, indicating that Croatia is a country with a low opioid consumption. Conclusion: Between 2007 and 2013, both consumption of analgesics and their cost in Croatia had an increasing trend. Comparisons with data from other countries, based on the published literature, indicate that analgesic consumption in Croatia is still relatively low. Calculation of the adequacy of opioid consumption indicated that Croatia is a country with low opioid consumption. Further studies are necessary for establishing whether current analgesic consumption in Croatia corresponds to patient needs. Keywords: pain, analgesic agents, prescription opioids, drug utilization, adequacy